Estudio técnico para la viabilidad de generación de energía por medio del ciclo rankine de cogeneración en Vereda San Luis, Macheta – Cundinamarca (2021)
This document presents, as its main objective, the technical viability of power generation through the Rankine cycle of cogeneration in the village of San Luis, Macheta - Cundinamarca, using the residual biomass produced in this municipality, given the constant inconveniences of power cuts electricity in the area, adds the excessive volume through the generation of organic waste from the completion of the harvest of legumes and forestry. Understanding the previous difficulties seeks to satisfy a need by mitigating a problem, it is important to highlight the possible ways to solve, of which, he perceives; Search for tangible information regarding waste, what calorific potential they give us and how to take advantage of it in a thermodynamic process.